2010
DOI: 10.1080/02640410903567785
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being elastic: Deflection of a badminton racket during a stroke

Abstract: The deflection profiles of a badminton racket during strokes performed by elite and world-class badminton players were recorded by strain gauges and subsequently analysed to determine the role of shaft stiffness in racket performance. Deflection behaviour was consistent in all strokes across all players, suggesting a controlled use of racket elasticity. In addition, all impacts occurred within 100 ms of each other, a duration in which deflection velocity provides an increase in racket velocity, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
3
0
1
Order By: Relevance
“…Values generally agreed with the past works that were done for motion capture of badminton racket smash stroke, as seen in [110,111]. Literatures have shown that top players are capable of using the elastic deflection of badminton racket to achieve a higher tip speed [112][113][114]. While it might be critical for racket dynamics, this experiment was only for observing an estimate to develop a launcher.…”
Section: Motion Analysis Of Racket Speedsupporting
confidence: 84%
“…Values generally agreed with the past works that were done for motion capture of badminton racket smash stroke, as seen in [110,111]. Literatures have shown that top players are capable of using the elastic deflection of badminton racket to achieve a higher tip speed [112][113][114]. While it might be critical for racket dynamics, this experiment was only for observing an estimate to develop a launcher.…”
Section: Motion Analysis Of Racket Speedsupporting
confidence: 84%
“…Badminton rackets are composed of a rigid handle and a flexible shaft. The proximal-distal sequence contributes by increasing racket velocity to produce a powerful stroke, that allows the maximization of momentum transfer at impact, including racket velocity [17]. Compared with other racket sports, badminton rackets are relatively flexible [18].…”
Section: спортивная тренировкаmentioning
confidence: 99%
“…In the badminton sports, the elasticity of badminton string is an important parameter to evaluate the hitting ability of a racket [16]. According to the literature review, most studies focus on the changes in MOE of badminton strings at different temperatures.…”
Section: Introductionmentioning
confidence: 99%